1984
DOI: 10.1039/f19848001705
|View full text |Cite
|
Sign up to set email alerts
|

Metachromasy in clay minerals. Sorption of acridine orange by montmorillonite

Abstract: The adsorption of acridine orange by H-, Na-, Mg-, Al-and Cu-montmorillonite has been studied by visible and infrared spectroscopy and by X-ray diffraction methods. Adsorption of the dye takes place by the mechanism of cation exchange. The maximum amount of adsorbed dye depends on the exchangeable metallic cation, decreasing in the order Na > H > Cu > Mg > Al. The adsorbed cationic dye is located in the interlayer space. Adsorption leads to metachromasy of the dye molecule and a shift of the absorption bands t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
1
2

Year Published

1988
1988
2000
2000

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 0 publications
3
39
1
2
Order By: Relevance
“…This result suggests that most MB molecules can exist as monomers on the clay in suspensions of low loading. Similar effects were also reported for planar acridine orange (Cohen and Yariv, 1984) and pyronin Y (Grauer et al, 1987), both of which resemble MB in molecular shape. The adsorption of CV in saponite produced a slight metachromasy similar to that observed for MB.…”
Section: Effect Of Synthetic Saponite On Absorption Spectra Of Cationsupporting
confidence: 63%
“…This result suggests that most MB molecules can exist as monomers on the clay in suspensions of low loading. Similar effects were also reported for planar acridine orange (Cohen and Yariv, 1984) and pyronin Y (Grauer et al, 1987), both of which resemble MB in molecular shape. The adsorption of CV in saponite produced a slight metachromasy similar to that observed for MB.…”
Section: Effect Of Synthetic Saponite On Absorption Spectra Of Cationsupporting
confidence: 63%
“…As a result of this rc interaction, band ct, which is due to it ~ 7t* transition, is perturbed and is replaced by band [3. This was shown to occur during the adsorption of AO by montmorillonite which is a dioctahedral smectite and gains its charge mainly from octahedral substitutions, but to a small extent also from tetrahedral substitutions (Cohen & Yariv, 1984). Now we show that metachromasy also occurs during the adsorption of AO by saponite.…”
mentioning
confidence: 68%
“…Based on the XRD results which are described later, and on the observations obtained using montmorillonite (Cohen & Yariv, 1984), it is suggested that monomeric cations in the first region are located in the interlayer space, parallel to the silicate layers, forming n interactions with Yariv, 1995). From the location of band ct two different types of clay-dye association can be inferred.…”
Section: Effect Of Na-saponite On the Absorption Spectrum Of Aomentioning
confidence: 99%
See 1 more Smart Citation
“…Because the observed d(001) value was only 13.5 ~, they ascribed the metachromasy to the interaction of the lone pair of electrons of the surface oxygens with the ~r electrons of the dye. The same observation and interpretation was put forward for acridine orange (Cohen and Yariv, 1984). Grauer et al (1984), however, did not detect metachromasy with rhodamine 6G because the C6HsCOOC2H 5 substituent of rhodamine 6G hampered an efficient interaction between the oxygens and the 7r electrons (the formulae of the dyes are given in Figure 1).…”
Section: Introductionmentioning
confidence: 92%